Rural Health Response and Community Preparedness for the Covid-19 Pandemic - Nita Arisanti; Trevino A Pakasi; Syarhan Syarhan (Faculty of Medicine, Public Health, and Nursing, 2020)
Covid-19 is a highly contagious disease and has infected more than seven million people worldwide. Deaths due to this disease have reached 418,000 deaths in June 2020.1 Based on data from the Indonesian Covid-19 Task Force, there were 172,053 cumulative cases with a death rate of 4.3% in Indonesia up to August 30, 2020.Indonesia is an archipelago country which has different geographical characteristics. Currently, access to basic healthcare and quality of basic health services has not reached all regions, especially those in underdeveloped, remote and archipelago areas. Health problems in rural areas become a concern for Indonesian government. This is because around 43% of people live in rural areas or around 116 million people. Government should pay attention to rural health problems as well as urban health. Likewise, during the Covid-19 pandemic rural area will face same problems to Covid-19.